Chronic Periodontitis and Cardiovascular Disease: A Controlled Clinical Trial. (May 2013) - Mariotti, G.; Quaranta, A.; Merli, M.; Holtzman, L. Paternò; Piemontese, M.
Cardiovascular disease is one of the leading causes of death worldwide. Controlled prospective studies and randomized clinical studies have shown that inflammation plays a major role in the pathogenesis of atherosclerosis, and that a chronic inflammatory systemic reaction increases the risk of cardiovascular, and cerebrovascular attacks. In recent years, many researchers have focused on defining a correlation between cardiovascular and periodontal diseases. The aim of the present study was to observe the effects of periodontal causal therapy on the level of specific inflammatory markers, such as C-reactive protein (CRP) and interleukin-6 (IL-6) levels, before and after non-surgical periodontal therapy. A total of 64 patients were enrolled in the present study. Among these, 26 patients were affected by cardiovascular disease and periodontal disease, (MCV-Perio test group), whereas 38 patients were only affected by cardiovascular disease, without periodontal disease, (MCV control group). The MCV-Perio group was then sub-divided into two additional groups: Treated MCV-Perio test group, treated with non-surgical phase I periodontal therapy; Not-Treated MCV-Perio test group, not treated with any periodontal therapy. A comprehensive periodontal treatment was carried out at baseline. The non-surgical therapy treatment was conceived according to Full Mouth Therapy (FMT) treatment protocol, consisting of various phases delivered in a very short time. Blood samples were collected at baseline and re-evaluated in order to assess periodontal and inflammation marker changes. All values were registered as an average ± standard deviation (x ± SD) and Wilcoxon-Mann-Whitney test was used. It is interesting to observe that the serum concentrations of IL-6 and hs-CRP were higher in the group with cardiovascular and periodontal disease compared to the group with cardiovascular disease alone. Non-surgical periodontal treatment determined a dramatic improvement in the levels of the systemic inflammatory markers. The results of the present study show that non-surgical periodontal therapy performed according to the Full Mouth Therapy protocol may prove beneficial in reducing the levels of inflammatory markers typically associated with heart disease. Because the two pathologies share a certain number of common risk factors, this may be a hindrance in the correct interpretation of the results. Therefore, further evidence, represented preferably with a randomized controlled clinical design is necessary to interpret the results correctly.